Secret médical et assurance de personnes : médecine asservie à l’assurance ou médecine au service de l’assurance ? - Homont, Laurent (Assurances)

(untitled) (HEC Montréal, 1996)
The very nature of personal questions asked by insurers requires that the answers be given special treatment to ensure the individual and his or her private life are respected. Reconciling the requirements of medical secrecy and the information insurers require to assess a risk is not easy and has given rise to a mutual distrust between physicians and insurers. For physicians, medical secrecy is essential and no departure must be permitted. Insurers who fear anti-selection see it is an obstacle to equitable risk assessment. In his article, Laurent Homont asks a fundamental question: is medicine subservient to insurance or is it at the service of insurance? He suggests establishing an impenetrable barrier between the medical and administrative spheres that come under the insurer. The delicate balance between the protection of insureds and insurers rests on the protection of the individual. To date, no report recommends departure from medical secrecy in favour of insurance companies. While the article deals with the French experience, it strikes a sensitive chord here in Canada.